The effectiveness of schema therapy in individuals who committed crimes: A systematic review - Sousa, Marta (2024)
Research suggests that individuals who commit crimes often exhibit various early maladaptive schemas (EMSs). EMSs are a broad and pervasive theme or pattern consisting of memories, emotions, cognitions, and bodily sensations concerning oneself and one’s relationships with others. Furthermore, EMSs play a crucial role in the onset and maintenance of different types of offending behaviors, highlighting the need to implement schema therapy (ST) for perpetrators. Therefore, the present systematic review assesses the effectiveness of ST for individuals who committed crimes. Four databases (PubMed, Scopus, Web of Science, and Scielo) were searched for studies examining the effectiveness of ST for individuals who committed crimes. Seventeen studies were identified, but only 15 met the criteria for inclusion. Results showed that ST can lead to beneficial effects in EMSs, schema modes, personality symptoms, and risk factors to commit crimes (e.g., cognitive distortions). However, the studies, besides being scarce, revealed some methodological limitations. ST is a promising therapy for individuals who committed crimes, despite the studies’ methodological shortcomings, which prevent us from drawing more firm conclusions. Although promising, more research is needed to enhance our understanding of the impact of ST therapies in forensic settings.